2020
DOI: 10.1016/j.chiabu.2020.104709
|View full text |Cite
|
Sign up to set email alerts
|

Child Maltreatment during the COVID-19 Pandemic: Consequences of Parental Job Loss on Psychological and Physical Abuse Towards Children

Abstract: Highlights Job loss increases risk for psychological and physical abuse during the pandemic. Positive cognitive reframing mitigates risk of job loss on physical abuse. Interventions targeting reframing may decrease risk for abuse during COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
362
2
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(410 citation statements)
references
References 40 publications
29
362
2
17
Order By: Relevance
“…While psychiatricrelated disorders attributed to the lockdown state have been widely reported in the adult and adolescent literature [36,37], rates of domestic violence and child abuse in particular, have not been adequately studied [15]. Studies on child maltreatment during the pandemic have reported that parental factors including job loss, burnout, anxiety and depression could be contributory factors [38,39]. This again, has practical implications on future lockdown states, where pediatric services must focus not only on managing the acutely unwell child, but also ensure that the mental and social wellbeing of families and children are cared for, particularly in vulnerable families [40].…”
Section: Discussionmentioning
confidence: 99%
“…While psychiatricrelated disorders attributed to the lockdown state have been widely reported in the adult and adolescent literature [36,37], rates of domestic violence and child abuse in particular, have not been adequately studied [15]. Studies on child maltreatment during the pandemic have reported that parental factors including job loss, burnout, anxiety and depression could be contributory factors [38,39]. This again, has practical implications on future lockdown states, where pediatric services must focus not only on managing the acutely unwell child, but also ensure that the mental and social wellbeing of families and children are cared for, particularly in vulnerable families [40].…”
Section: Discussionmentioning
confidence: 99%
“…If parents use emotion-focused coping strategies, they may seek emotional support or counseling services when they are experiencing negative emotions. Given the complex and increased stress during the COVID-19 pandemic, parents that have few appropriate coping strategies may be more likely to maltreat a child (Abramson, 2020;Lawson et al, 2020). Previous literature has shown that abusive parents report a significantly higher level of parenting stress (Miragoli et al, 2016), and this may interfere with their ability to cope effectively with parenting difficulties, thus increasing the likelihood of child maltreatment (McPherson et al, 2009).…”
Section: Coping Strategiesmentioning
confidence: 99%
“…By understanding the nature of the stressors, increasing parental resources, and changing parental perceptions and coping strategies, we may reduce the risk of child maltreatment (Abramson, 2020;Lawson et al, 2020;Ngai et al, 2016). As COVID-19 has transformed our lives in several ways, and it may become a new normal for us, parents and children need to adjust their perceptions about life changes caused by COVID-19 and make corresponding adaptations.…”
Section: Implications For Practicementioning
confidence: 99%
“…A prior study found that families with low incomes were more likely to have an adult in the household facing a health problem (Neckerman et al, 2016), which may also explain, in part, why COVID-19 deaths may be skewed toward poorer populations (Finch & Finch, 2020), in addition to risk of more frequent exposure to the virus in higher volumes in essential jobs (Garfield et al, 2020). Many are cautioning that all of these abrupt shifts for families are increasing stress and household conflict, exacerbating mental health challenges, and increasing unhealthy reliance on substances-ultimately putting children in more precarious situations with more potential negative impacts in the long-term (Child Welfare League of Canada [CWLC], 2020; Duan et al, 2020;Lawson et al, 2020;Presse Canadienne, 2020).…”
Section: Determining Which Services Are "Essential"mentioning
confidence: 99%
“…The way the pandemic will impact child protection systems is not yet fully clear, and may not be for some time. While calls to child protection systems went down in the initial months of the pandemic (e.g., Jonson-Reid et al, 2020;Robson, 2020), the risk of abuse, neglect, and sexual exploitation may have increased (Campbell, 2020;Klein, 2020;Lawson et al, 2020;Rosenthal et al, 2020;Teo & Griffiths, 2020; UNICEF, 2020) but not necessarily be reported due to families' decreased interaction with potential reporters, such as teachers and other school professionals who are typically a substantial source of referrals to child protection systems (e.g., Joh-Carnella et al, 2020; Public Health Agency of Canada, 2010). In particular, many child protection researchers and practitioners worry about the compounding impacts of shut-down measures on families who were already in vulnerable economic situations before the pandemic began (Alliance for Child Protection in Humanitarian Action, 2020; CWLC, 2020; Sistovaris et al, 2020).…”
Section: Determining Which Services Are "Essential"mentioning
confidence: 99%